Rainbow technology for a rainbow people : e-business capacity development for the CARICOM - Singh, Alwyn Didar (Commonwealth Secretariat LondonGB, 2001)
Places in perspective the importance of e-Business for developing countries such as those of the Caribbean. Analyzes the Caribbean's e-readiness focusing on aspects such as connectivity; e-leadership; security; human capital; and, e-business capital. Addresses, based on this analysis, the need for regional initiatives in this area. Suggests that electronic commerce affects the business environment at national, regional and global levels, and generates major opportunities, and new challenges, for market growth and development for jobs, industries and services. Recommends an action-plan and e-business capacity project for CARICOM.